Peran American Military Industrial Complex dalam Konflik Bersenjata di Timur Tengah - Ajie Mahar Muhammad (Jurnal ICMES, 2017)
The Middle East countries, such as Iran, Iraq, Lebanon, Syria, Yemen, Bahrain, Egypt, Turkey, or other countries, seemed to endlessly suffered security and political conflicts. In some countries, the conflict even leads to armed fightings, for example in Iraq, Syria and Yemen. Every day, the medias broadcast the development of the armed conflict in the Middle East, as if telling that this conflict is going to last forever. This phenomenon raises a question, what causes the Middle Eastern conflict to be prolonged? This article addresses the relations between the conflict and the phenomenon of neoliberalism which becomes the main driver of global economy. Using the concept of Military-Industrial Complex, this article argues that there are giant capitalist actors who maintain this condition so they can get huge profits due to the long-drawn armed conflict.